OPTIMISING FRENCH PRONUNCIATION IN SON ET INTONATION COURSE THROUGH SHADOWING METHOD SUPPORTED BY DIGITAL AUDIO-VISUAL MEDIA - Riza Harani Bangun; Setia Rini; Nabila Hasri Ainun; Aksendro Maximilian; Resa Permata Sari (JETA (Journal of English Teaching and Applied Linguistic), 2026)
This study examines the effectiveness of the shadowing method, integrated with digital audio-visual media, in optimising phonological competence development within the Son et Intonation (Sound and Intonation) course for first-semester students of the French Language Education Study Program at Universitas Lampung, Indonesia. The primary concern addressed is the suboptimal phonological proficiency of beginning learners, as evidenced by a class mean pre-test score of 66.07, with the majority of participants classified within the Very Low and Low performance categories. Employing a qualitative action-based research design, the study implemented five interrelated procedural stages: initial phonological competence assessment, shadowing instructional design development, digital audio-visual media production, classroom implementation, and evaluative post-test measurement. Thirty first-semester students participated in four progressively structured shadowing variants, muted shadowing, whisper shadowing, whisper-full shadowing, and full shadowing using authentic native speaker recordings as primary input models. Results indicated significant gains across all five rubric assessment dimensions: Pronunciation, Liaison & Enchaînement (sound linking), Intonation & Accentuation, Rhythm, and Fluency. The class mean post-test score surpassed the target threshold of 75.00, accompanied by a substantial reduction in the proportion of students in the Very Low and Low categories. These findings confirm that the shadowing method, when systematically supported by purpose-designed digital audio-visual media, effectively strengthens phonological competence and establishes a structured foundation for the development of oral communicative skills toward the B2 proficiency target specified in the Cadre européen commun de référence pour les langues (CECRL; Common European Framework of Reference for Languages).